Penentuan Waktu Baku dengan Metode Stopwacth Time Study Studi Kasus Depot Air Syam - Asri Nurhasanah; Ibramgara, Bratama; Hidayaturrahman, Taufik (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Depot Air Syam is a service company that produces mineral water. However, often these targets cannot be met, so companies consider whether to revise for those company targets. In order for the company to continue to survive and win the increasingly fierce competition, it needs these advantages in addition to being obtained through increased productivity. One of the ways that companies do is by measuring standard time. The purpose of this study is to help companies to consider the need for revision of company targets. The observation method is the method used in this study, resulting in a standard time in the gallon water refilling process of 241.4 seconds. This time is obtained from the average cycle time of 164.4 seconds.